Emoticons Unveiled: A Multifaceted Analysis of Their Linguistic Impact - Ike Revita; Farah Anindya Zalfikhe; Helen Boholano; Nguyen Thanh Tuan; Balazs Huszka; Zulfakhri Dt. Majo Datuk (JURNAL ARBITRER, 2023)
This study aims to thoroughly investigate the linguistic impact of emojis and emoticons in modern written communication. This work attempts to shed light on these digital symbols’ linguistic structure, social implications, and evolution through a multidisciplinary research method. A mixed-methods approach was used in the research, integrating interdisciplinary viewpoints with quantitative and qualitative analyses. A vast amount of data was gathered from various digital communication channels, such as email exchanges, messaging apps, and social media. A sizable collection of text messages with emojis and emoticons was assembled. Emotional cons and emojis were categorized using linguistic analysis, breaking down their structure into visual components and repeating patterns. Their grammatical and syntactic effects on written language were also evaluated in this investigation. The findings indicate that using emojis in writing positively correlates with emotional expressiveness. This implies that when people wish to express emotions and subtlety in their messages, they typically utilize more emoticons. They enhance digital etiquette, reduce misunderstandings, improve emotional connection, and foster cross-cultural understanding. Emoticons are a global visual language that helps people communicate, create empathy, and navigate digital communication.